Assessment of patient perceptions concerning a community pharmacy-based warfarin monitoring service - Jennifer Waitzman; Debbie Pruss Hiller; Macary Weck Marciniak; Stefanie Ferreri (University of Minnesota Libraries Publishing, 2012)
Objective: To assess patient perceptions of a North Carolina community pharmacy-based warfarin monitoring service. Methods: Prospective study of patients 18 years of age and older, who filled a prescription for warfarin, in one of five Raleigh area community pharmacies, between May 1, 2010 and October 31, 2010. A 14 item survey, along with a self-addressed stamped envelope, was mailed to 330 identified patients. The survey inquired about details of current anticoagulation monitoring services, interest in utilizing a local community pharmacy for this service, and confidence in a pharmacist-managed program. Results: 26% of surveys were returned. 48% of surveyed individuals responded that they would be interested in having their warfarin monitoring performed by a trained pharmacist in a community pharmacy setting. Conclusion: Many participants responded that the community pharmacy would be more convenient than or as convenient as their current location. This may be a new clinical service that could be offered in certain community pharmacies.   Type: Original Research